Molecules Involved in the Sperm Interaction in the Human Uterine Tube: A Histochemical and Immunohistochemical Approach - Milla-Brito, L; Orihuela-Diaz, P; Godoy-Guzman, C (Luigi Ponzio e figlio Editori, 2023)
In humans, even where millions of spermatozoa are deposited upon ejaculation in the vagina, only a few thou-sand enter the uterine tube (UT). Sperm transiently adhere to the epithelial cells lining the isthmus reservoir, and this interaction is essential in coordinating the availability of functional spermatozoa for fertilization. The binding of spermatozoa to the UT epithelium (mucosa) occurs due to interactions between cell-adhesion molecules on the cell surfaces of both the sperm and the epithelial cell. However, in humans, there is little infor-mation about the molecules involved. The aim of this study was to perform a histological characterization of the UT focused on determining the tissue distribution and deposition of some molecules associated with cell adhesion (F-spondin, galectin-9, osteopontin, integrin αV /β3 ) and UT’s contractile activity (TNFα-R1, TNFα-R2 ) in the follicular and luteal phases. Our results showed the presence of galectin-9, F-spondin, osteopontin, integrin αV/β3, TNFα-R1, and TNFα-R2 in the epithelial cells in ampullar and isthmic segments during the menstrual cycle. Our results suggest that these molecules could form part of the sperm-UT interactions. Future studies will shed light on the specific role of each of the identified molecules. © the Author(s), 2023 Licensee PAGEPress, Italy.